Perceptions of Students to Open and Distance Learning of Review Classes in a Review Center in the Philippines - Lopez, Aaron Bryan A. (International Journal on Open and Distance e-Learning, 2019)
The Commission on Higher Education (CHED, 2007) defined review centers as hubs offering programs or courses of study intended to refresh and enhance knowledge, competencies, and skills of students who have already studied in any formal school to prepare them for upcoming licensure examinations given by any license-giving body such as those given by the Professional Regulation Commission (PRC). There were several review centers that offered open and distance learning aside from their brick-and-mortar classes in several locations in the Philippines. This had been possible due to technological advances that led to the distribution of knowledge using internet-enabled services. Review for Global Opportunities (RGO) Review Center, a CHED-accredited review center, was one of the leading review centers in the field of psychometrician review in the Philippines with having over 10 awards for the past 3 years and it has been offering the face-to-face classes in their review program for aspiring psychometricians. This 2018, RGO offered a home-based study program and delivered online. The study examined the perception of students enrolled in the said distance learning review program for aspiring psychometricians by RGO Review Center using a survey questionnaire partially adopted from Alam, Waqar, Zaman, Shehzadi, and Mehmood (2012) to provide a better understanding to predict student satisfaction, especially in online learning environments.